Outcomes and Revision Rates Following Pediatric Ventriculoperitoneal Shunt Surgery: A Retrospective Study at Misrata Medical Center (2021‒2025) (مجلة البحوث الأكاديمية, 2026)
Background: Ventriculoperitoneal (VP) shunting is the most common treatment for hydrocephalus in children. However, shunt-related complications and revision rates remain high.Objective: To evaluate the demographic profiles, indications, surgical approaches, complication rates, and revision causes among pediatric patients who underwent VP shunt surgery at Misrata Medical Center between January 2021 and December 2025.Methods: This retrospective study included 144 pediatric patients who underwent VP shunt placement. Data on age, sex, indication for shunting, valve type, surgical approach, complications, and revision causes were collected and analyzed.Results: Among the 144 patients (102 males and 42 females), congenital hydrocephalus was the leading indication for VP shunting (47.9%). A total of 49 patients (34%) required at least one revision surgery. The primary reasons for the first revision were obstruction (49%) and infection (34.7%), respectively. The majority of first revisions (63.3%) occurred within six months of the initial surgery. Infants under one year of age had a higher revision rate. The overall mortality rate was 11.8%, with higher rates observed in patients who required multiple revisions.Conclusion: VP shunt surgery in our pediatric population is associated with a significant risk of complications, primarily obstruction and infection, leading to a high revision rate. Age under one year is a key risk factor for shunt failures. These findings underscore the need for enhanced preventative strategies and close postoperative monitoring to improve patient outcomes